Synthesis, Optical Energy Gap and Gas Sensing Properties of TiO2 Doped Cr2O3 Thin Films - Ali, Nihad K.; Sallal, Ikhlas H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2026)
Thin films of Titanium dioxide (TiO2) doped Chromium oxide (Cr2O3) with a thickness of nm and a doping ratio of (0.2, 0.4, 0.6, 0.8)% employed on glass and n-type porous silicon substrates by using Pulsed laser ablation technique. A Cr2O3: TiO2/PSi heterojunction for a gas sensor device was synthesized with Nd: YAG laser with 1064nm wavelength with 500 pulses of laser energy 600mJ. The effect of the dopant concentration ratios on absorption coefficient ,optical energy gap and gas sensing properties such as sensitivity, responsivity and recovery times in the presence of 400ppm concentration of H2S gas, were studied and discussed. The doped samples showed increased absorption coefficient values with higher doping concentrations. The optical band gap ranged from 3.95 eV-3.71 eV for the pure and TiO2 doped Cr2O3 thin films. The optimum sensitivity was (166.24%) when the doping ratio of TiO2 was 0.6% when exposed to an H2S-reduced gas at an operating temperature of 100οC.